Human Milk Oligosaccharides Are Stable Over One-Week of Lactation and Over Six-Hours Following a Standardized Meal. (7th June 2021) - Berger, Paige; Plows, Jasmine; Jones, Roshonda; Alderete, Tanya; Schmidt, Kelsey; Bode, Lars; Fields, David; Goran, Michael
Abstract: Objectives: Our prior studies revealed that human milk oligosaccharides (HMOs) have numerous health benefits for nursing infants, and can also change dynamically over 24 months of lactation. However, the extent to which HMOs vary over days of time and also in response to acute factors such as maternal diet has not been established. The aims of this study were to determine the stability of HMO concentrations over 7-days, and in response to a standardized meal and sugar-sweetened beverage (SSB) over 6-hours. Methods: Lactating mothers were enrolled at 6 weeks. Participants received in-person instructions and materials to complete procedures at home. In the first experiment (N = 11), mothers pumped a fasted sample of human milk at 7:00 AM for 7-consecutive days. In the second experiment (N = 33), mothers pumped a fasted sample of human milk at 6:00 AM. Mothers then consumed a standardized meal plus SSB provided by the study team. Thereafter, mothers pumped a non-fasted sample every hour for 6-consecutive hours. Samples were analyzed for nineteen HMOs. One-factor repeated-measures ANOVA was used to test changes in HMOs. Results: There were no significant changes in any of the HMOs over 7-consecutive days, including 2'-fucosyllactose (2'FL) (interaction, P = 0.99), lacto-N-fucopentaose I (LNFPI) (interaction, P = 0.36), disialyl-lacto-N-tetraose (DSLNT) (interaction, P = 0.99), and lacto-N-neotetraose (LNnT) (interaction, P = 0.90). Further, there were no significant changes in any of the HMOs following a standardized meal plus SSB, as 2'FL (interaction, P = 0.12), LNFPI (interaction, P = 0.95), DSLNT (interaction, P = 0.66), and LNnT (interaction, P = 0.67) did not change in response to the diet intervention over 6-consecutive hours. Conclusions: Our findings reveal that HMOs are stable over one-week during early lactation, and are not acutely affected by maternal food and SSB consumption. Funding Sources: National Institutes of Health (HD098288, HD080444, and DK056341); Harold Hamm Diabetes Center at the University of Oklahoma Health Sciences Center.